"Circles of support": social isolation, targeted assistance, and the value of "ageing in place" for older people. (29th April 2020) - Bolton, Emma; Dacombe, Rod
Abstract : Purpose: This study aims to explore the experiences of older people "ageing in place", focussing on the implementation of "Circles of Support", a pilot intervention aimed at mitigating the risk of hospitalisation amongst socially-isolated older people. Design/methodology/approach: The study draws on qualitative research, taking in semi-structured interviews with participants in the intervention and with community networkers involved in delivering the programme. Findings: The research provides indicative findings supporting the idea that social isolation is linked to health issues amongst older people. It also suggests that targeted interventions can go some way to mitigating this problem. The findings presented here also indicate the importance of a deeper understanding of the lived experiences of socially-isolated older people in designing and delivering interventions. Originality/value: The study contribution is in three areas. It presents findings based on the pilot programme relating to the experiences of older people at risk of social isolation and provides an indication of the value of interventions aimed at tackling social isolation, connecting these to the risk of hospitalisation.